The Importance of Religion for Human Health - Abdul Aziz Romdhoni (Penerbit Hellow Pustaka, 2024)
Religion and health science have the potential to support each other, for example, people who want to carry out the Hajj pilgrimage (Islam) need the role of medical personnel to carry out general health check-ups so that the Hajj pilgrimage can run well. If you remember the code of ethics that applies in the field of medicine or nursing, to provide health services without discrimination based on race, ethnicity, religion and customs. This means that medical personnel must not act in discrimination against patients. Religion has a strategic function to be a source of moral strength for both patients in the healing process and health workers. For religious people, they hold the belief that God's treatment is in accordance with human expectations of Him.